The Mackenzie Basin: An Alternative Approach to Dene and Metis Archaeology - Hanks, Christopher C.; Pokotylo, David L. (ARCTIC, 1989)
More active Dene involvement in archaeology and a shift in research strategies from culture history to ethnoarchaeology are gradually changing the way that the archaeological record of the Mackenzie Basin is studied. This is occurring at a time when the Dene are tired of being simply the object of inquiry and are becoming inquirers in their own right. Recent community-based ethnoarchaeological and archaeological research has involved Native elders as consultants in project design, data collection and analysis, and the training of Native youth as crew members. Collaboration between archaeologists and northern Native people poses new questions of mutual concern that integrate oral histories, material culture, contemporary land use and settlement patterns, and archaeological data. At the regional level of analysis, new hypotheses evaluate present and past interrelationships of Native place-names, resources, travel routes, and camp locations. Traditional Native knowledge of spatial usage and feature function allows more accurate archaeological definition of site structure and settlement types at both pre- and post-European contact sites.Key words: Athabaskans, Metis, ethnoarchaeology, ethnogeography, Mackenzie Mountains, Mackenzie Basin, Mountain Dene, Slavey, field training Mots clés: Athabaskans, Métis, ethnoarchéologie, ethnogéographie, monts Mackenzie, bassin du Mackenzie, mont Déné, Slavey, formation sur le terrain